THERAPY COST ANALYSIS AND EFFECTIVENESS OF TREATMENT OF OUTPATIENT WITH TYPE 2 DIABETES MELLITUS AT RSUD SLEMAN YOGYAKARTA - Pratiwi Dinaryanti; Achmad Fudholi; Tri Murti Andayani (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetes is a chronic disease that can significantly increase a person›s risk of having complications. These complications not only cause the inability of the body that will affect the quality of life, but also need big cost. This research was conducted to analyze the costs and effectiveness of therapies of outpatient with type 2 diabetes mellitus. A crosssectional observational method was performed on 100 patient who were admitted to the Department of Endocrinology of the Sleman Hospital between December 2010 to January 2011. Data were taken in 2 ways: concurrent and retrospective, with accidental sampling technique. The subject of this research were outpatient with type 2 diabetes mellitus at RSUD Sleman Yogyakarta, who have used the antidiabetic therapy for at least three months of therapy before the quality of life measurement. The costs that are measured are direct medical costs, antidiabetic costs, complication costs, laboratory examination costs, and administration costs. The effectiveness of treatment parameters was measured based on the percentage of patients with fasting blood glucose level (GDP) and post-prandial blood glucose (GDPP) which reached the target in the third month of therapy, and achievement of the quality of life research subjects. The Lowest total cost of therapy was the use of glibenclamide, it was 49.730,00, the highest total cost of therapy was the use of insulin, it was Rp. 411.045,50. T test results with 95% confidence level indicates that the patient characteristics and medication adherence complications affect the patients quality of life, whereas non-pharmacological therapy (exercise and diet) did not significantly influence the patients quality of life. The results of measurements of quality of life showed metformin achieved the best quality of life than the other antidiabetic, i.e. 72.53. Based on the effectiveness of the three parameters (measurement of quality of life and levels of GDP and GDPP) note that metformin therapy tend to be more effective compared with other antidiabetic therapies.Key words: Diabetes mellitus type 2, cost analysis, effectiveness, antidiabetic, RSUD Sleman Yogyakarta.